Speech communication related to the process of traditional therapeutic efforts among the Baduy people in Lebak Regency, Indonesia - Heriyanto,; Krisnawati, Ekaning; Suryani, Elis; Sujatna, Eva Tuckyta Sari; Pamungkas, Kasno (Penerbit Universiti Kebangsaan Malaysia, 2020)
Speech communication employs various and complex expressive ways ranging from linguistic to extralinguistic features, and it studies the interaction between the speaker and listener, including interpersonal interaction like the one between a patient and his or her traditional healer. This article discusses some of the issues concerning the language used in the traditional healing process which uses Baduy mantra among the community. Therefore, this study is interdisciplinary in nature and the overall approach is qualitative. Methodology-wise, this research is conducted using discourse analysis and an ethnography of communication. There are two aims from this study, which are: 1) to point out the linguistic and extralinguistic features utilised in the communication component related to activities contributing to the healing process; 2) to describe the meaning of the mantra used in the process of therapeutic practices; 3) to reveal the patterns of the Baduy medicinal mantra perceived from an ethnography of communication point of view. The results of the research indicate that the mimetic and expressive functions of mantra reflect the role of traditional therapeutic efforts as well as interpersonal relations among the members of the community. The extralinguistic elements are employed to arouse suggestion in order to support the effort of a treatment.